2013
DOI: 10.1016/j.amjcard.2013.01.272
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Patients Living Without a Partner or Spouse to Being Physically Active After Acute Coronary Syndromes (from the PULSE Accelerometry Substudy)

Abstract: Living alone is associated with adverse outcomes after an acute coronary syndrome (ACS). One potential mediator of the relationship between partner status and outcomes after an ACS is physical activity. To evaluate the association of partner status with physical activity after an ACS we analyzed data from 107 participants enrolled in the Prescription Use, Lifestyle, and Stress Evaluation Study, a prospective observational study of post-ACS patients. Accelerometers were employed to measure physical activity fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
9
1
1
Order By: Relevance
“…However, little is known about the influence of living alone in older patients on the clinical outcome after AMI. In previous studies, living alone was reported to be associated with increased risk of cardiovascular disease 1-4 and poorer clinical outcomes after AMI [5][6][7][8][9][10] . However, most studies enrolled not only patients receiving primary PCI but also those with lytic therapy or those not receiving reperfusion therapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, little is known about the influence of living alone in older patients on the clinical outcome after AMI. In previous studies, living alone was reported to be associated with increased risk of cardiovascular disease 1-4 and poorer clinical outcomes after AMI [5][6][7][8][9][10] . However, most studies enrolled not only patients receiving primary PCI but also those with lytic therapy or those not receiving reperfusion therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Living alone was reported to be associated with increased risk of cardiovascular disease 1-4 and poorer clinical outcomes after acute myocardial infarction (AMI) [5][6][7][8][9][10] . However, the proportion of patients who had undergone percutaneous coronary intervention (PCI) was small in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients participated in an ancillary study in which they were provided with an Actical accelerometer (Philips Respironics, Bend, Oregon) at or soon after discharge (3). Patients were asked to continuously wear the device on their non-dominant wrist and to return the device one month later.…”
mentioning
confidence: 99%
“…A daily or most days of the week, 30 minute moderate physical activity, could contribute to serious improvements in cardiovascular health (29). Marital status has been also stated that positively influence physical activity and participation in cardiac rehabilitation programmes (31,32).…”
Section: Physical Activity Status and Secondary Acs Preventionmentioning
confidence: 99%